Frequência de mutações no gene CFTR e indicações do tratamento com moduladores em pacientes com fibrose cística - Lima, Eliandra da Silveira de (2020)
Objective: the aim of the study was to determine the distribution of the CFTR mutations in a group of patients followed at a cystic fibrosis (CF) center in the South of Brazil, as well as describing the candidate mutations to use specific mutation drugs. Methods: this is a descriptive cross-sectional study. The study included patients followed at a CF reference center, with a clinical diagnosis of CF and with both alleles identified with pathogenic mutations. Results: ninety-two patients were assessed. The most prevalent mutations were F508del, R1162X, G542X, and N1303K. Regarding the patients with indication for specific-mutation for the use of modulators, 69.6% are candidates for the use of Elexacaftor/Tezacaftor/Ivacaftor (Trikafta®), 44.6% for the use of Tezacaftor/Ivacaftor (Symdeko®) and 35.9% for the use of Lumacaftor/Ivacaftor (Orkambi®). For the use of Ivacaftor (Kalydeco®), only 2 patients (2.2%) are candidates, in accordance with the Brazilian agency approval. According to FDA, 10 patients would be candidates for Ivacaftor (10.9%). Conclusions: mutations class I and II, which are related to a major severity of the illness, were identified in 135 of 184 alleles (73.3%). In this study, more than 2/3 of the patients are candidates for the use of CFTR modulators therapy.